Métodos de geração de vazões mensais e suas influências sobre a curva de garantia versus vazão regularizada em reservatórios do Estado do Ceará - Farias, José Alexandre Moreira (2003)
Researchers have developed for years many discharge generation techniques, some based on sophisticated mathematical procedures and others only on observations of the discharge regime behavior. It is known today that the option for one discharge generation model interferes significantly in the reservoirs design and so one can erroneously estimate the reservoirs dimension due to a firm yield evaluated through the use of a mistaken discharge generation methodology. This dissertation generated three synthetic series of flows using three different methodologies – Thomas & Fiering with Clarke modification, Thomas & Fiering with Clarke modification and Matalas transformation and Monte Carlo Method associated with the Svanidze Method of Fragments – getting the firm yield diagrams from the generated series based on the mentioned methodologies and comparing them with the ones made through the use of the historical inflows series. An analysis of the relative error between the firm yield of each methodology as compared with the historical series was also performed, for the case of 90% reliability – the most used reliability level in hydrologic studies. Finally, it was concluded that among the studied methods of discharge generation the one that most reproduced the nature of the hydrologic event in discussion – the regimen of the reservoirs water inflows – was the Monte Carlo Method associated with the Svanidze Method of Fragments.